IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA DI MTs SYARIF ABBAS KABUPATEN TANAH - Rahmiyatul Ahda; Agus Sujarwo; Garum (UNISAN JURNAL, 2025)
This study aims to describe the implementation of character education management in developing positive student interests, attitudes, and behaviors at MTs Syarif Abbas in Tanah Bumbu Regency in the 2024/2025 academic year. This research is motivated by the importance of strengthening student character at the madrasah level as an effort to develop individuals with noble character, discipline, and high learning motivation. The research approach used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results indicate that character education management at MTs Syarif Abbas is implemented through three main stages: planning, implementation, and evaluation. During the planning stage, the school develops a character strengthening program integrated into the curriculum, intracurricular, co-curricular, and extracurricular activities. During the implementation stage, character values ​​are instilled through teacher role models, routine religious activities, the practice of greetings and smiles, and the strengthening of discipline through school rules. Character-based learning is also implemented by integrating religious values, responsibility, and cooperation into the learning process. Meanwhile, the evaluation stage is carried out through monitoring student behavior, journal attitudes, and character assessments by subject teachers and homeroom teachers. Overall, the implementation of character education management has been proven to positively contribute to increasing students’ interest in learning, fostering polite and responsible attitudes, and encouraging positive behavior in daily life within the madrasah environment. Thus, character education at MTs Syarif Abbas is effective and relevant to national education goals.